Penetapan Kadar Mineral Besi (Fe) dan Kalsium (Ca) pada Biji Buah Markisa Konyal dengan Metode Spektrofotometri Serapan Atom (SSA) - Tisa Mandala Sari; BA Martinus; Sherly Oktaviani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Research has been conducted on the determination of iron (Fe) and calcium (Ca) mineral levels in konyal passion fruit seeds (Passiflora ligularis Juss) using the Atomic Absorption Spectrophotometry (AAS) method. The purpose of this study was to determine the levels of Iron (Fe) and Calcium (Ca) in konyal passion fruit seeds. This study consisted of qualitative analysis and quantitative analysis. Qualitative tests for iron (Fe) were carried out by color reaction tests using ammonium thiocyanate and potassium hexacyanoferrate solutions, for calcium (Ca) using ammonium oxalate solution and flame tests, positive results were obtained indicating the presence of iron (Fe) and Calcium (Ca) levels in the sample. Quantitative analysis was measured by Atomic Absorption Spectrophotometry (AAS) method using Fe cathode lamp at a wavelength of 248.3 nm, and Ca with a wavelength of 422.7 nm, carried out with 3 repetitions so that the average iron (Fe) content was obtained at 0.0899 ± 0.000383 mg/g and calcium (Ca) at 3.2009 ± 0.033252 mg/g.